IMPLEMENTATION OF A REAL-TIME MONITORING SYSTEM FOR HIGH ECONOMIC ORNAMENTAL PLANTS USING THE ODO GREK APPLICATION - Odo, Klaodius (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
The increasingly rapid development of science and technology also has an impact on the development of technology used by society in carrying out its daily activities. Internet technology encourages the development of information technology applications, both website-based and Android-based. Developing Android-based applications is also made easier with the presence of APP Inventor. APP Inventor was developed by MIT (Massachusetts Institute of Technology) in 2011. This is an application for developing website-based Android applications that can be accessed online. The system developed allows real-time monitoring of ornamental plants via an Android application. Data such as soil moisture and temperature can be accessed anytime and anywhere, making it easier for plant owners to take the necessary actions. Users of sensors connected to the ESP32 and integrated with Firebase are proven to provide accurate and reliable data. Tests show that this system is capable of sending and receiving data quickly and accurately, so that users always have the latest information about the condition of their plants. The implementation of this system uses components that are relatively affordable and easy to obtain. The Android application developed is also designed with a user-friendly interface, so that it can be used by various groups without requiring in-depth technical knowledge.